Adult-Onset Sandhoff Disease in a Filipino Patient: Asymmetric Weakness, Whole HEXB Gene Deletion, and Coexisting MYH7 Pathogenic Variant. (26th June 2022) - Beecher, Grayson; Liewluck, Teerin; Milone, Margherita
Abstract : Objective: To describe a Filipino patient with adult-onset Sandhoff disease manifesting with an atypical asymmetric lower motor neuron syndrome due to a novel whole HEXB deletion in trans with a pathogenic missense variant and with a coexisting MYH7 pathogenic variant. Methods: We performed clinical, laboratory, myopathologic, and genetic evaluation with next-generation sequencing in the proband and targeted mutational analysis in an asymptomatic sibling. Results: A 59-year-old Filipino woman presented with 15 years of slowly progressive, asymmetric, proximal-predominant, lower greater than upper extremity weakness, mildly elevated creatine kinase, and generalized cerebellar atrophy. Serum total β-hexosaminidase was significantly reduced, and hexosaminidase A percentage was increased. We identified a novel HEXB whole gene deletion in compound heterozygosity with a pathogenic missense variant (c.1513C>T, p.Arg505Trp) previously described in 1 patient with adult-onset Sandhoff disease. The patient, with a family history of cardiomyopathy, has a coexisting MYH7 pathogenic variant (c.3134G>A, p.Arg1045His), causative of cardiomyopathy but without cardiac involvement, likely due to variable penetrance. Myopathic features were absent from skeletal muscle biopsy. Discussion: This patient expands the genotypic, phenotypic, and ethnic spectrum of Sandhoff disease and highlights challenges generated by low-penetrant pathogenic variants, especially when considering a potentially polygenic phenotype.